1995
DOI: 10.1136/oem.52.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural evaluation of Venezuelan workers exposed to inorganic lead.

Abstract: Objectives-To assess neurobehavioural effects of low exposure to lead, 43 workers from a lead smelter and 45 workers from a glass factory were evaluated with the World Health Organisation neurobehavioural core test battery (NCTB) in a cross sectional study. Methods-The NCTB comprises a questionnaire and seven tests that measure simple reaction time, short term memory (digit span, Benton), mood (profile of mood states), eye-hand coordination (Santa Ana pegboard, pursuit aiming II), and perceptual speed (digit-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 16 publications
(6 reference statements)
4
41
0
4
Order By: Relevance
“…However, this inconsistency disappears in a meta-analysis by Meyer-Baron and Seeber [18], which is based on the studies mentioned. The finding of unaffected reaction time by lead is in accordance with the findings of Haenninen et al [12], Maizlish et al [16] Campara et al [5] and Repko et al [22]. They are in conflict with Williamson and Teo [29].…”
Section: Discussionsupporting
confidence: 94%
“…However, this inconsistency disappears in a meta-analysis by Meyer-Baron and Seeber [18], which is based on the studies mentioned. The finding of unaffected reaction time by lead is in accordance with the findings of Haenninen et al [12], Maizlish et al [16] Campara et al [5] and Repko et al [22]. They are in conflict with Williamson and Teo [29].…”
Section: Discussionsupporting
confidence: 94%
“…Baker et al (1983) reported impaired verbal concept formation, memory, and visual/motor performance among workers with PbB >40 μg/dL. Similar findings were reported in a cohort of 43 Venezuelan workers from a lead smelter who had a mean-employment duration of 4 years and a mean PbB of 42 μg/dL (Maizlish et al 1995). The authors observed a significant association between altered mood states and current, peak, and timeweighted average (TWA) blood lead levels.…”
Section: Health Effectssupporting
confidence: 72%
“…Many human and experimental studies during past decades have demonstrated adverse effects on the central nervous system (CNS) after chronic exposure to inorganic lead [3][4][5]. Neuropsychological symptoms and cognitive deficits have been the main manifestations of milder adverse effects, and although several studies have demonstrated the neuropsychological effects of current lead exposure [6][7][8][9][10][11] only a few studies have examined cognitive abilities after long-term exposure has ceased [12,13]. Results from the two latter studies are controversial, and it remains unclear whether reduced cognitive abilities from chronic low-level lead exposure are reversible or not [11].…”
Section: Introductionmentioning
confidence: 99%